Parameter Genetik Jagung Populasi Bisma pada Pemupukan yang Berbeda. II. Ragam dan Korelasi Genetik Karakter Sekunder - Sutoro, Sutoro; Bari, Abdul; Subandi, Subandi; Yahya, Sudirman (Jurnal AgroBiogen, 2007)
Genetic Parameter of Secondary Traits of Corn in BismaPopulation under Different Fertilizer Application. II. GeneticVariance and Correlation of Secondary Traits.Sutoro, Abdul Bari, Subandi, and Sudirman Yahya. Themagnitute of secondary traits of corn could affect the cornyield. Genetic parameter value of secondary traits areimportant in plant breeding, especially in selection program.Genetic parameter could be used for estimation of correlatedresponse by involving value of genetic correlation andgenetic variance. Value of genetic parameter is differentamong population and environment. Genetic parameter ofsecondary traits on Bisma population under 3 different levelof fertilizer application were studied in Bogor. Result of thestudy showed that addtive genetic variance of ASI, chlorofil,seed number, amount of green leaves and LAI at floweringstage greater than dominant variance. Conversely, additivegenetic variance of green leaf number and LAI at maturingstage, and leaf senescene are lower than dominant variance.ASI has greatest heritability among secondary traitsunder three level of fertilizer application. Positive geneticcorrelation was found between grain yield under low fertileizerapplication and ASI under high level fertilizer applicationor between grain yield under high level of fertilizer applicationand ASI under low level fertilizer application.